The effects of ethephon on the rooting of cuttings - Mudge, Kenneth W., author; Swanson, Bert T., advisor; Workman, Milton, committee member; Hartley, David E., committee member; Ross, Cleon, committee member (Colorado State University. Libraries, 1976)
Ethylene has been shown to promote rooting in a number of species of herbaceous and woody plants. Because ethylene is a gas it is impractical for treating cuttings. Ethephon, a liquid which releases ethylene to plant tissue, offers a practical means of treating cuttings with ethylene. This research was designed to investigate the effect of ethephon solutions at various pH's on the rooting of cuttings and on ethylene levels within cuttings. Woody cuttings of Salix caprea, Ribes alpinum, Salix alba, Potentilla fruticosa, Rosa hybrida, Rosa laxa, Forestiera neomexicana and Populus deltoides were treated with unbuffered solutions of ethephon and rooted under intermittent mist in a greenhouse. The latter five species were also treated with IBA and ethephon plus IBA. Response to the treatments was measured as percent rooted, number of roots per cutting, and root dry weight per cutting. Ethephon promoted rooting of S. caprea and P. fruticosa only. In no case was ethephon as effective as IBA. Light grown mung bean cuttings were treated with solutions of ethephon, IBA and the combination of both. Treatment solutions were unbuffered, or buffered at pH 3.7, 5.7 and 7.4. Ethylene levels in treated cuttings were determined by p.as chromatography and rooting was measured as number of roots per cutting. Ethephon treatment resulted in increased tissue ethylene levels with increasing solution pH, but no effect on rooting occurred at any pH. IBA treatment had no effect on tissue ethylene levels, but it did strongly promote rooting.
Covers not scanned.
Keywords: Plant growth promoting substances; Plant cuttings; Growth (Plants)